Design and implementation of a broad-band high gain low noise amplifier for 3G/4G applications - Ahmed M. Abdelmonem; Ahmed S. I. Amar; Amir Almslmany; Ibrahim L. Abdalla; Fathi A. Farag (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The main aim of the paper is designing and implementing a broadband low-noise-amplifier (LNA) based on compensated matching network techniquein order to get high stable gain, low noise figure, low cost and smaller sizefor 3G/4G communication system applications at 2 GHz with bandwidth 600MHz. The Advanced Design System simulates the proposed circuit (ADS).The implementation was done with a class A bias circuit and a low noise transistor BFU 730F with a lower Noise Figure (NFmin) 0.62 dB. Collectorcurrent is measured to be 5.8mA and base current is 19.1μA with a supply voltage of 2.25V. The new design proposed a (NFmin) of 0.62 dB with a 17.8dB high stable amplifier gain. The microstrip lines (MSL) and compensated matching network techniques were used to improve the LNA’s stability and achieve a good result. The LNA board is implemented and assembled on the FR4 botton layer material. The results are virtually non existence equivalent between the simulated and the measured results.